Some biological aspects of the swimming crab Portunus pelagicus (Linnaeus, 1766) (Decapoda: Portunidae) in NW Arabian Gulf - Abdul-Sahib, I.M. (Mesopotamian Journal of Marine Sciences, 2022)
The blue swimming crab Portunus pelagicus (Linnaeus, 1766) was collected from Al-Fao region, southern Iraq. The carapace width for the adult males, was ranging between 80.15 and 120.34 mm, and for the adult females was ranging between 60.1 and 100.69 mm. The carapace length for the adult males ranged between 40.03 and 50.93 mm, while those of the adult females were 30.84-50.14 mm. The chelae length ranged between 50.21 and 90.06 mm and between 40.77 and 60.57 mm for males and females, respectively.